An investigation of the effects of organisational communication on work outcomes within agriculture research institutes in Nigeria - Oso Oluwatoyin Aduke; Lawal-Adebowale Okanlade Adesokan; Aduradola Remi Rebecca; Adigun James Kehinde (Agricultura Tropica et Subtropica, 2020)
The study investigated the effects of organisational communication on work outcomes (job satisfaction, affective commitment and quit-intentions) of agriculture research personnel from six research institutes in Nigeria. Further, the mediational role of job satisfaction was determined among the constructs. Simple random sampling technique was used to elicit information from 209 researchers of the selected research institutes. Data were collected through a well-structured questionnaire and analysed using hierarchical regression and Sobel tests. Results obtained from hierarchical regression analyses indicated that organisational communication was related to job satisfaction (b = 0.18, P < 0.01), affective commitment (b1 = 0.20, P < 0.01) and quit-intentions (b1 = – 0.18, P < 0.01). Sobel test indicated that job satisfaction partially mediated the organisational communication-affective commitment relationship (Z = 5.42, P < 0.05). Similarly, job satisfaction was a partial mediator of the organisational communication – quit-intention relationship (Z = 4.13, P < 0.05). This is an indication that increased organisational communication fosters personnel’s satisfaction with job, improves affective commitment and reduces intents of quitting the organisation. Evidence of partial mediation revealed that job satisfaction may not be the only mediator of the predictor-criterions linkages.